Evaluating CBN tool life in hardened boring operations in long overhangs - Wallyson, Thomas; Fülöp, Zsombor; Szilágyi, Attila (Design of Machines and Structures, 2020)
This work aims to monitor the tool wear process using optical microscopy, so that the lifespan of the tool could be verified. The tool overhang was varied until it reached a limit (the deepest hole it could machine). The results show that, when the tool overhang is within its stability range, the flank wear of the tool is accentuated when the tool overhang outreaches its stability limit.